2013
DOI: 10.1017/s0021859613000890
|View full text |Cite
|
Sign up to set email alerts
|

Spacing between rows: effects on water-use efficiency of double-cropped wheat and soybean

Abstract: SUMMARYProductivity and water resource usage efficiency are crucial issues in sustainable agriculture. The aims of the present research were to compare and evaluate the soil moisture content (SMC), evapotranspiration (ETa), yield, water-use efficiency (WUE), and net return of winter wheat (Triticum aestivum L.) and soybean [Glycine max (L.) Merr.] under different plant population distribution patterns and to identify the possible ways to improve water utilization. Using the same plant population for a given cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Reduced spacing between rows in a same plant density results in better plant distribution in the area. In this way, intraspecific competition is reduced due to greater equidistance between plants, and greater water efficiency (ZHOU et al, 2015). However, De Bruin and Pedersen (2008) reported that the soybean response to spacing reduction varies according to crops, localities, cultivars, sowing time, and soil management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced spacing between rows in a same plant density results in better plant distribution in the area. In this way, intraspecific competition is reduced due to greater equidistance between plants, and greater water efficiency (ZHOU et al, 2015). However, De Bruin and Pedersen (2008) reported that the soybean response to spacing reduction varies according to crops, localities, cultivars, sowing time, and soil management.…”
Section: Resultsmentioning
confidence: 99%
“…One of the objectives of using narrow row spacing is to reduce the time the crop intercepts most of the solar radiation, optimizing canopy photosynthetic capacity (DE BRUIN;PEDERSEN, 2008). In addition, adjusting spacing may change root distribution in the area, water use efficiency, weed competition (ZHOU et al, 2015), morphology CHERNEY, 2011;WERNER et al, 2017), and soybean yield (HANNA et al, 2008). Some recent research showed that the effects of reduced spacing on yield vary according to cultivars and sowing time, with positive effects on indeterminate cultivars that are quite compact and sown at the beginning of the harvest PROCÓPIO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The proper use of irrigation should be considered in order to obtain greater water use efficiency (Zhou et al, 2015).…”
Section: Total Yield and Yield Components In Cornmentioning
confidence: 99%
“…An uneven spatial and temporal distribution of precipitation makes wheat vulnerable to water deficits during growing development (DENG et al, 2006;ZHOU et al, 2015). The Tai'an region receives precipitation that reaches a maximum level of 200 mm in the growing season of winter wheat.…”
Section: Introductionmentioning
confidence: 99%